Electromagnetic Production of Hypernuclei - Terry Mart (Institut Teknologi Bandung, 2007)
We review the progress in current understanding of the hypernuclear production through electromagnetic interaction. The motivation behind the interest in this investigation, i.e., the hyperon-nucleon force, is briefly overviewed. Special attention is given for the kaon productions on a deuteron and 3He. We also discuss some advantages of electromagnetic production of hypernucleus compared with the hadronic one.